Morbidade cirúrgica pós-biópsia de linfonodo sentinela e esvaziamento axilar: estudo comparativo em mulheres com e sem preservação do nervo intercostobraquial - Beatriz Pifano Soares Ferreira (2008)
Purpose: The aim of this study is to evaluate the morbidity after sentinel node biopsy (SNB) and axillary dissection with (AD-NP) or without preservation the intercostobrachial nerve (AD-NS). Methods: A study was performed on 108 patients divided in three groups: SNB (n=35), AD-NP (n=36) and AD-NS (n=37). We evaluated the incidence of sensory loss, pain, lymphedema, seroma formation and infection in the arm homolateral of the breast surgery. Semmes-Weinstein monofilaments were used to assess the sensory loss; brachial perimetry were usedto evaluate the presence of lymphedema; pain questionnaire were applied. Results: At least one complication after surgery was reported by 45/108 (41,7%) patients. Pain was the outcome more frequently reported by patients. Significant difference was observed in three groups only regarding sensory loss (p=0,04). Pain, lymphedema, and sensory loss were more frequently found in AD-NS group. No significant difference was observed between SNB and AD-NP groups. Semmes- Weinstein monofilaments showed preservation of cutaneous sensitivity in 28/35patients from SNB group, in 25/36 patients from AD-NP group but in only 10/37 patients from AD-NS group (p<0,001). Conclusions: The patients from the AD-NP had less sensory loss, with the results similarly to the patients from SNB group. The ICB section leads to the sensory loss that can change from reduction to loss of protective sensation. The Semmes-Weinstein monofilaments allowed to assess the degree of sensory loss from the AD-NS group.